Kinerja Kepala Sekolah Sebagai Supervisor dalam Membina Peningkatan Profesionalisme Guru di Madrasah Ibtidaiyah Raudlotul Hamdi Rembang Kecamatan Rembang Kabupaten Pasuruan - Juwairiyah Juwairiyah; Ashari Ashari (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
This research uses a qualitative type of research, with a case study research design at MI Roudlotul Hamdi Rembang. Data collection was carried out using interviews, observation and documentation methods. Data analysis techniques through data collection, data reduction, data presentation and drawing conclusions. Data validity techniques, using source and theory triangulation.Based on research data, it was obtained: The performance of school principals in improving teacher professionalism includes developing teacher professionalism through Subject Teacher Conferences (MGMP). The supervision techniques used include class visits and class observations. The school principal as supervisor must be able to carry out various supervision and control to improve the performance of the teaching staff to the maximum.